ERGONOMIC ASSESSMENT AND RISK REDUCTION OF AUTOMOBILE ASSEMBLY TASKS USING POSTURAL ASSESSMENT TOOLS - Srikanth P Chakravarthya, Subbaiah.K.M Shekar. G.L (International Journal of Research Science and Management, 2015)
Automotive is one of the fast growing industries which involve the design, development and manufacturing of motor vehicles. However, it has its own impediment as the interaction between man and machinery pose several health hazards. Work related musculoskeletal disorders (MSDs), low back injuries and poor body postures are the most common problems occurring in the automobile industries. The aim of this study was to identify the risks of work related MSDs and eliminates the same. The Rapid Upper Limb Assessment (RULA) & Rapid Entire Body Assessment (REBA) methods were used to find out the scores of working postures for the existing process .Engineering control actions were implemented to those process with high risk. Processes were reassessed using the tools. Substantial risk reduction was achieved.